THE IMPACT OF REHABILITATION EXERCISES ON DEVELOPING AND IMPROVING STRENGTH AND RANGE OF MOTION IN NECK MUSCLES AMONG PATIENTS WITH DISC HERNIATION - Asst.Prof.Doc Ali Awad Jabbar (Proximus Journal Publishing, 2024)
The importance of the research lies in developing rehabilitation exercises for treating cervical disc herniation and enhancing the strength and range of motion of the affected muscles. The study aimed to develop rehabilitation exercises to increase strength and flexibility for individuals with cervical disc herniation, and then evaluate the impact of these exercises on strength and flexibility in pre-post assessments. A sample of athletes aged 35-40 with cervical disc herniation was selected and randomly divided into two groups: an experimental group undergoing specifically designed rehabilitation exercises and a control group receiving physiotherapy at specialized centers.
Keywords: specialized; undergoing; rehabilitation